Pengaruh Electronic Word of Mouth (e-WOM) di Media Sosial terhadap Keputusan Menonton pada Film Spider-Man - Ramadhany, Valda Ayu; Illahi, Azizun Kurnia (Universitas Brawijaya, 2022)
This research examines the influence of Electronic Word of Mouth on the decision to watch the movie Spider-Man: No Way Home. The study aims to determine whether Electronic Word of Mouth (e-WOM) has an impact on the decision to watch Spider-Man: No Way Home, as assessed through three dimensions of Electronic Word of Mouth: Intensity (X1), Valence of Opinion (X2), and Content (X3), along with the purchasing decision as the dependent variable (Y). An explanatory quantitative method was employed in this study, with data collected through an online questionnaire, online comments, or reviews about the film Spider-Man: No Way Home on social media. The sampling technique used in this research was purposive sampling, and multiple linear regression analysis was applied for data analysis. The results indicate that the Theory of Planned Behavior can explain the decision to watch the movie made by the respondents. Furthermore, the dimensions of Intensity (X1), Valence of Opinion (X2), and Content (X3) collectively contribute to 46.5% of the variance in the purchasing decision variable (Y). Intensity (X1) and Content (X3) are dimensions of the independent variables that significantly influence, while the Valence of Opinion dimension (X2) does not significantly affect the decision to watch.